Salibu Rice Cultivation in Tungro Endemis Region - Khaerana Hafid; I Nyoman Widiarta; Achmad Gunawan; Arif Muazam (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2023)
Salibu is modified ratoon rice which has advantages in economic and time-saving. Tungro disease is one of probable handicap for salibu to be controlled in their endemic area. Rice virus tungro disease is caused by Rice Tungro Bacilliform Virus (RTBV) and Rice Tungro Spherical Virus (RTSV) which are transmitted by leafhopper. The research goals are to know the growth of leafhopper population and the spread of the tungro disease in salibu and conventional rice farming system as well as their effect on yield. The research was conducted in split plot experiment and designed in a randomized block design. The main plot were 1) salibu system and 2) conventional system (non-salibu). The subplots were   varieties 1) TN1 (sensitive variety), 2) Ciherang (commonly used by the farmer), and 3) Inpari 36 (tungro new resistant variety). The results revealed that the tungro attack rate, dry milled grain yield, and 1000 dry grain weight were significantly higher in conventional cultivation than salibu (P < 0.05). The number of leafhopper populations tended to be higher in salibu system than in conventional system. The number of natural  enemies did not show a particular pattern related to green leafhopper's presence. The Shannon Wiener diversity index for natural enemies ranged from low to medium. Regarding to the results, salibu system is not recommended yet in the tungro endemic areas. Keywords:   Salibu, rice tungro virus disease, green leafhopper, natural  enemies